Comparison of the effect of ball and bar attachment designs on retention and stability of mandibular implant-supported overdentures - Sabouri, Abolfazl; Barjini, Negar; Tabatabaian, Farhad (Journal of Dental School, 2019)
Objectives The present study evaluated the effect of bar and ball attachment designs on retention and stability of a mandibular overdenture supported by four implants. Methods An edentulous mandibular acrylic resin model with four implants in the anterior part of the ridge (A, B, D and E) was fabricated. A metal framework simulating the overdenture was also fabricated. Totally, 30 overdentures were divided into three groups based on the attachment design; BL: Four ball attachments in A, B, D and E positions; BB: One bar attachment between B and D positions and two ball attachments at positions A and E; BR: Bar attachments between the positions A, B, D and E with two posterior extensions. To evaluate the retention and stability of the overdenture, tensile dislodging forces were applied in three directions of vertical, oblique and anterior- posterior by a universal testing machine. One-way ANOVA and Tukey’s HSD test were performed to analyze the data. All tests were carried out at 0.05 level of significance. Results There were statistically significant differences between the groups in the peak load (P < 0.001). The peak load values for vertical, oblique and anterior-posterior dislodging forces were the highest for BL with 49.38 ± 2.19 N, 52.19 ± 1.44 N, and 49.03 ± 5.89 N, respectively, while these values were the lowest for BR with 29.78 ± 2.52 N, 12.10 ± 0.45 N, and 6.26 ± 0.45 N, respectively. Conclusion The attachment designs affected the retention and stability of mandibular implant-supported overdentures.